LASTING BIOLOGICAL EFFECTS OF EARLY ENVIRONMENTAL INFLUENCES : V. VIABILITY, GROWTH, AND LONGEVITY - Dubos, Rene (The Rockefeller University Press, 1969)
The effects of neonatal influences on the growth and longevity of mice were studied by using animals derived from a highly inbred germfree colony that had been reassociated with a microbial flora free of known pathogens. The size of the animals at weaning time could be conditioned predictably by manipulating the diet of their mothers during gestation and lactation or by shortening or lengthening the period of lactation. A deficient diet during gestation or during lactation decreased the metabolic efficiency of the adult animal, even if it was fed an optimum diet after weaning. The effect was greatest when malnutrition occurred during both pregnancy and lactation. In contrast, an optimum diet during gestation and lactation rendered the animal less susceptible to the depressing effects of nutritional deficiency during adult life. A marked and lasting growth depression could be reproducibly achieved by contaminating newborn mice orally with an unidentified enterovirus. But neonatal infection with enterobacteria or mycobacteria even though severe, did not significantly alter the growth rate. Regardless of its initial cause, the depression of the growth rate during the preweaning period persisted throughout the whole life span of the animals, even when they were placed under optimum sanitary and nutritional conditions after weaning. Agencies (nutritional or infectious) which brought about a depression of whole body weight also affected the absolute and relative sizes of the various organs, especially of the brain. By manipulating neonatal influences, it was possible to produce at will in a given colony of highly inbred mice a family of strikingly different growth curves. This could be done without causing the death of any animal or affecting longevity.